A state-of-the-art review of the sharing economy: Scientometric mapping of the scholarship - Klarin, Anton; Suseno, Y. (2021)
Using a dataset of 2,229 scholarly outputs from the Web of Science on the sharing economy (SE), our scientometric review provides a taxonomy of the current research on the SE in terms of their contributions, theories, and methods utilized in existing studies. The review also highlights a typology of the inter-related concepts of the SE. We demonstrate four clusters of existing research: freelance work and its implications, transportation and solutions for the sustainable development of the SE, user experience and collaborative consumption, and the SE in the context of hospitality and tourism. We suggest future research directions in terms of the need to investigate the SE implications on a wider set of stakeholders including businesses and governments, to examine the SE value creation in terms of business models and entrepreneurship, to investigate the SE in other industries and sectors, and to conduct large-scale empirical studies in this research domain.